(untitled) (Scientific journal of the Fergana State University, 2022)
This article studies the properties of the Kampe de Feriet function of two fourth-order arguments. Integral representations and a system of differential equations in partial derivatives of hypergeometric type, which is satisfied by the indicated function, are proved.